Enhancing Learner Involvement In Sgbs: A Case Study Of One School In Mangaung Metropolitan Municipality. - Dumako, Itumeleng, Ishmael (Central University of Technology, Free State, 2019)
This study focuses on the enhancement of learner participation in school governance. South African School’s Act 84 of 1996 stipulates that learners should legally form part of School Governing Bodies (SGBs). However, members in the SGB have opted to ignore such stipulations. Learners are excluded from participating in school governance because of individual perceptions that other members in the SGB have about them. They are left behind when training for the entire SGB is conducted, thus making it difficult for them to take part in meetings that are filled with riddling jargon and engagements of policies. This study revealed that attitudes of elderly governors towards learners are the center of challenges faced by learners. Concomitantly, the insufficient participatory chances given to learners and lack of capacity building made the cut to prime challenges faced by learners. I took a stance, as a researcher that learners are excluded from SGBs and indeed the outcomes proved my notion right. In an attempt to stick to its own objectives, the study addressed the research question: How do we enhance learner participation in the SGB? Critical Emancipatory Research (CER) was adopted as the theoretical framework and Participatory Action Research (PAR) as a methodology. To analyze the data gathered, Critical Discourse Analysis (CDA) was utilized. During the initial stages of the research, a forum was developed to deal with challenges facing learners in the SGB and subsequently come up with strategies to remedy that. The forum engaged as equal partners in the research as they embarked into discourse in an attempt to eliminate a socially unjust situation that was facing them. As a community, co-researchers were able to cooperatively work towards a common goal. They were able to identify problems that were facing them and ultimately remedied them on their own. It is through the same forum that this study can promulgate its strategies that will aid in enhancing learner participation in SGBs.
Dissertation